Analisis Bibliometrik Perkembangan Penelitian Sistem Teknik pada Bidang Teknik Mesin Menggunakan VOSviewer dan Biblioshiny - Rezaabdulrahin Tanjung; Rafi Ahmad; Muhammad Rizky (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the development of engineering system research in the field of mechanical engineering using a bibliometric approach. Data were collected from the Scopus database using the query TITLE-ABS-KEY (